Molecular data suggests a Pliocene – Early Pleistocene divergence date for the common and pygmy hippopotamus - Kardos, Michael C.; Velmurugan, Sindhu; Janecka, Jan E. (Frontiers in Ecology and Evolution, 2023)
Hippopotamid phylogeny has proven difficult to resolve with proposed relationships between extant and fossil species receiving mixed levels of support. Of particular interest is the divergence between the two extant hippopotamid species, the well-known common hippopotamus (Hippopotamus amphibius) and the enigmatic pygmy hippopotamus (Choeropsis liberiensis). Previous studies have relied on morphological and fossil evidence to identify the ancestral species at the core of this divergence and its timing. In this study, we assembled a molecular matrix of 26 nuclear gene sequences from eleven ungulate species with two primates as an outgroup. We used a Bayesian relaxed molecular clock approach to reconstruct a calibrated time tree for Cetartiodactyla and estimate the divergence date between the common and pygmy hippopotamus. While previous morphological studies have estimated this event to have occurred sometime during the late Miocene (between 11.6 and 5.3 million years ago), our nuclear gene-based estimates suggest a more recent split of about 4.04 Ma (95% confidence interval: 8.31 – 1.97 Ma) via RelTime-ML or 2.4 Ma (95% confidence interval: 3.1 – 1.6 Ma) via MCMCTree. These more recent estimates correspond with the Pliocene – early Pleistocene epochs and align most closely with the results of previous genomic studies. We discuss how our results compare with previous estimates based on both morphological and molecular studies, some of which extend the predicted range of this divergence date even further back in time. Our results suggest a different path of evolution for the understudied pygmy hippopotamus and reveal that morphological evidence alone may not resolve the correct hippopotamid phylogenetic and time trees. We suggest that the common and pygmy hippopotamus may be phylogenetically closer than once believed. Our results also call for further studies to develop a combined approach incorporating both molecular and morphological evidence to reach a consensus on the evolutionary patterns and timing that led to modern hippopotamid evolution.